Evaluation of cellular activity in response to sleep deprivation by a comprehensive analysis of the whole mouse brain - Urushihata, Takuya; Goto, Mio; Kabetani, Keiko; Kiyozuka, Mai; Maruyama, Shiho; Tsuji, Shogo; Tada, Hirobumi; Satoh, Akiko (Frontiers in Neuroscience, 2023)
Sleep deprivation (SD) causes several adverse functional outcomes, and understanding the associated processes can improve quality of life. Although the effects of SD on neuronal activity in several brain regions have been identified, a comprehensive evaluation of the whole brain is still lacking. Hence, we performed SD using two different methods, gentle handling and a dedicated chamber, in targeted recombination in active populations 2 (TRAP2) mice crossed with Rosa-ZsGreen reporter mice and visualized cellular activity in the whole brain. Using the semi-automated post-imaging analysis tool Slice Histology Alignment, Registration, and Cell Quantification (SHARCQ), the number of activated cells was quantified. From the analysis of 14 brain regions, cellular activity was significantly increased in the olfactory areas and decreased in the medulla by the two SD methods. From the analysis of the further subdivided 348 regions, cellular activity was significantly increased in the vascular organ of the lamina terminalis, lateral hypothalamic area, parabigeminal nucleus, ventral tegmental area, and magnocellular reticular nucleus, and decreased in the anterior part of the basolateral amygdalar nucleus, nucleus accumbens, septohippocampal nucleus, reticular nucleus of the thalamus, preoptic part of the periventricular hypothalamic nucleus, ventromedial preoptic nucleus, rostral linear nucleus raphe, facial motor nucleus, vestibular nuclei, and some fiber tracts (oculomotor nerve, genu of corpus callosum, and rubrospinal tract) by the two SD methods. Two subdivided regions of the striatum (caudoputamen and other striatum), epithalamus, vascular organ of the lamina terminalis, anteroventral preoptic nucleus, superior colliculus optic layer, medial terminal nucleus of the accessory optic tract, pontine gray, and fiber tracts (medial lemniscus, columns of the fornix, brachium of the inferior colliculus, and mammillary peduncle) were differentially affected by the two SD methods. Most brain regions detected from these analyses have been reported to be involved in regulating sleep/wake regulatory circuits. Moreover, the results from the connectivity analysis indicated that the connectivity of cellular activity among brain regions was altered by SD. Together, such a comprehensive analysis of the whole brain is useful for understanding the mechanisms by which SD and/or sleep disruption affects brain function.